Religion and politics of belonging in digital times: youth religiosity in focus - Astrid Mattes; Miriam Haselbacher; Katharina Limacher; Christoph Novak (Frontiers in Political Science)
Political responses to growing diversity are often characterised by one-dimensional attempts to pin down a collective identity. In stark contrast, we see that young people in diverse urban areas negotiate their multiple, flexible belonging both on- and offline. Young believers, in particular, experience their religion as a powerful category of difference, often related to discrimination or rejection on grounds of their religiosity. Here, the discursive construction of belonging, as discussed in the concept “politics of belonging,” is useful to grasp the formations of in- and out-groups on religious grounds. Individual negotiations of belonging always resonate with political ideas of the nation and the secular and with discourses of inclusion and exclusion. The discursive and structural maintenance of boundaries that separate people into those who belong and those who do not is more than a top-down process. It concerns and involves individuals and their identifications. Here, digital spaces, as increasingly relevant spaces of public exchange, provide new terms for identity work. In this paper, we are interested in the specific role of digital spaces for identification among young believers and for processes of boundary drawing. Building on social media tours and qualitative in-depth interviews with 41 young believers of different religious traditions, we explore individual negotiations of belonging in digital spaces, as well as negotiations in relation to religious communities and political concepts. We find that digital spaces reinforce certain boundaries (e.g., among religious traditions) whereas they facilitate the blurring of others (e.g., confessional structures). This is guided by algorithms following the logic of attention economy that structures social media as well as by the conscious search for digital possibilities of inclusion. At the same time, the online world enables various forms of countering experienced exclusions. Consequently, we identify strategies of young believers to navigate complex discourses of being religious in a secular world and the role of the digital within it. We discuss these empirical findings on religious youth against the theoretical backdrop of a “Politics of Belonging” and we explore options towards a theoretical concept to grasp digital politics of belonging.